Bike Intelligent Training Systems (BITs) / Mohd Akmal Hadi Mazlan and Muhammad Alif Mansor - Mazlan, Mohd Akmal Hadi; Mansor, Muhammad Alif (2015)
On the bicycle, there have some of additional equipment that help cyclist in term of safety features likes bike helmet, reflector light, and speedometer. Furthermore, bike should have many the new innovation of additional equipment to improve the safety features. For example, if the cyclist cycling over the speed limit especially when cycling down the hill with maximum speed that could not brake properly for stopping because bicycle is lighter transportation that will easy accident happen. On fitness exercise, cyclist need one of system to monitoring whole their training season for the speed and healthy level (pulse (rate). To further improvise the productivity of bicycle, we came out with the idea of Bike intelligent Training System (BITs). This project is made to innovation the existing Bike Speed Sensor Equipment by improvement a safety features on bicycle and monitoring the health of pulse rate cyclist. This project will focus on two new specification in terms of safety features on bicycle and monitoring the health of cyclist. By monitoring the pulse rate when cycling activities, cyclist can be maintain their health which doing the exercise properly and flow their body health condition not to force it. BITs is design for monitoring speed of cycling in KM/H. For the improvement of safety features on bicycle, BITs also can warning or notifying by the cyclist if they over speed limit to inform the cyclist to slow down their speed for avoid any accident when cycling in highest speed. Lastly, for all the additional equipment on bicycle should be waterproof suitable when raining, small and lighter.